2016
DOI: 10.1177/1545968315624777
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pain and Pain Management on Motor Recovery of Spinal Cord–Injured Patients

Abstract: Background Approximately 60% of patients suffering from acute spinal cord injury (SCI) develop pain within days to weeks after injury, which ultimately persists into chronic stages. To date, the consequences of pain after SCI have been largely examined in terms of interfering with quality of life. Objective The objective of this study was to examine the effects of pain and pain management on neurological recovery after SCI. Methods We analyzed clinical data in a prospective multicenter observational cohort stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 45 publications
1
30
0
Order By: Relevance
“…For medications that interact in the central nervous system or systems associated with neurological recovery (e.g., cardiovascular), there is an urgent need to establish drug safety and inform acute care management practices. The potential for some of these medications (e.g., gabapentinoids) to enhance neurological recovery has also recently been examined [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…For medications that interact in the central nervous system or systems associated with neurological recovery (e.g., cardiovascular), there is an urgent need to establish drug safety and inform acute care management practices. The potential for some of these medications (e.g., gabapentinoids) to enhance neurological recovery has also recently been examined [41,42].…”
Section: Discussionmentioning
confidence: 99%
“… 26 Pregabalin has been shown to reduce anxiety in patients suffering from poststroke pain. 27 Other clinical studies showed that treatment with gabapentin significantly improved motor function following spinal cord injury 28 and reduced dystonia severity in children. However, its effect on locomotor function following pain induction in rodents is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant medication records can also identify targets for drug repurposing. For example, a concomitant medication for treating neuropathic pain was found to be unintentionally beneficial for muscle strength recovery after spinal cord injury 3 4. This could lead to drug repurposing to maximise neurological outcomes 5…”
Section: Introductionmentioning
confidence: 99%